Poverty and agency among children in urban China - Yang, L; Walker, RL; Zhang, G (Bristol University Press, 2023)
Scholars of childhood typically view children as agentic; poverty researchers, aware that poverty reduces children’s life-chances, may be tempted to consider them as victims. Adults experiencing poverty report feelings of powerlessness, and, by analogy, poverty may reduce children’s agency. However, comparatively little is known about the impact of poverty on child agency or the extent to which children use their agency to mediate the effects of poverty. Therefore, 55 low-income children from two Chinese schools were invited to participate in group discussions and qualitative interviews spread over several hours. Considering poverty to be multidimensional, children identified that their agency was restricted both by poverty and their status as children but argued that they were not without agency. This was confirmed in interviews with parents and teachers. Six strategies were identified that children use to ameliorate poverty’s effects. The strategies group into three pairs, the first strategy in each pair reflecting a child’s decision to accommodate to their circumstances with the second being an attempt to alter them. The first pair (norm adaptation and active communication) comprised coping strategies addressing the present; the second pair (self-improvement and self-sacrifice) were expressions of constructive agency; and the third pair (lowered expectations and rebellion) were partially acts of despair. Giving greater recognition to children’s attempts to improve the lives of their families and themselves may lead to more effective modes of policy intervention.